Effect of water content components on desiccation and recovery in Sphagnum mosses - Hájek, Tomás; Beckett, Richard P (Annals of botany, 2008)
BACKGROUND AND AIMS: The basic parameters of water relations were measured in Sphagnum mosses. The relationships of these parameters to the photosynthetic response to desiccation and the ecology of these mosses were then tested. METHODS: The water relations parameters of six Sphagnum species (mosses typical of wet habitats) and Atrichum androgynum (a moss more typical of mesophytic conditions) were calculated from pressure-volume isotherms. Photosynthetic properties during and after moderate desiccation were monitored by chlorophyll fluorescence. KEY RESULTS: When desiccated, the hummock-forming species S. fuscum and S. magellanicum lost more water before turgor started dropping than other sphagna inhabiting less exposed habitats (73 % compared with 56 % on average). Osmotic potentials at full turgor were similar in all species, with an average value of -1.1 MPa. Hummock sphagna had clearly more rigid cell walls than species of wet habitats (epsilon = 3 x 55 compared with 1 x 93 MPa). As a result, their chlorophyllous cells lost turgor at higher relative water contents (RWCs) than species of wet habitats (0 x 61 compared with 0 x 46) and at less negative osmotic potentials (-2 x 28 compared with -3 x 00 MPa). During drying, Phi(PSII) started declining earlier in hummock species (at an RWC of 0 x 65 compared with 0 x 44), and F(v)/F(m) behaved similarly. Compared with other species, hummock sphagna desiccated to -20 or -40 MPa recovered more completely after rehydration. Atrichum androgynum responded to desiccation similarly to hummock sphagna, suggesting that their desiccation tolerance may have a similar physiological basis. CONCLUSIONS: Assuming a fixed rate of desiccation, the higher water-holding capacities of hummock sphagna will allow them to continue metabolism for longer than other species. While this could be viewed as a form of 'desiccation avoidance', hummock species also recover faster than other species during rehydration, suggesting that they have higher inherent tolerance. This may help them to persist in drought-exposed hummocks. In contrast, species growing in wet habitats lack such strong avoidance and tolerance mechanisms. However, their turgor maintenance mechanisms, for example more elastic cell walls, enable them to continue metabolizing longer as their water contents fall to the turgor-loss point.
Keywords: fluorescence; Bryophyta; chlorofyl; Sphagnopsida; rašeliníky; voda; Fluorescence; tlak; Photosynthesis; Water; Chlorophyll; fotosyntéza; Pressure